2015
DOI: 10.1063/1.4929641
|View full text |Cite
|
Sign up to set email alerts
|

Effect of substrate rotation on domain structure and magnetic relaxation in magnetic antidot lattice arrays

Abstract: Microdimensional triangular magnetic antidot lattice arrays were prepared by varying the speed of substrate rotation. The pre-deposition patterning has been performed using photolithography technique followed by a post-deposition lift-off. Surface morphology taken by atomic force microscopy depicted that the growth mechanism of the grains changes from chain like formation to island structures due to the substrate rotation. Study of magnetization reversal via magneto optic Kerr effect based microscopy revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 40 publications
1
13
1
Order By: Relevance
“…To overcome the additional pinning, the reversal field increases for the MAL arrays. This in principle is a general behavior for MAL arrays irrespective of their anisotropy and architecture 9 , 10 , 12 , 13 . However the shape of the loops (shown in Fig.…”
Section: Resultsmentioning
confidence: 72%
See 3 more Smart Citations
“…To overcome the additional pinning, the reversal field increases for the MAL arrays. This in principle is a general behavior for MAL arrays irrespective of their anisotropy and architecture 9 , 10 , 12 , 13 . However the shape of the loops (shown in Fig.…”
Section: Resultsmentioning
confidence: 72%
“…It is observed that although in case of the Co/Pt MAL arrays with PMA the reversal is nucleation dominated, however, the overall nature of the bubble domains is similar to its parent continuous thin film. It should be noted that, this behavior is different when comparing the domains of MAL arrays having in-plane anisotropy to their parent thin films 9 , 10 .
Figure 3 ( a – c ) and ( d – f ) are the domain images at - H S , H N , and H C , for samples ES1 and ES2, respectively.
…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Here the normalized intensity as a function of time basically reflects the net magnetization relaxation of the sample. Amongst various raised models to explain magnetization relaxation phenomena Fatuzzo-Labrune model is extensively used for FM thin films [38][39][40][41][42][43]. However, the approximation of single energy barrier made in this model does not hold for a real thin film which consists of a distribution of energy barrier with defects and inhomogeneity throughout the surface.…”
Section: Relaxation Dynamicsmentioning
confidence: 99%